Partner protections in HIV cure-related trials involving analytical treatment interruption: Updated toolkit to mitigate HIV transmission risk - Karine Dubé; Thomas J. Villa; William Freshwater; Brittney Mauk; Annette Rid; Michael J. Peluso (Elsevier, 2024)
Analytical treatment interruptions (ATIs) are widely used to evaluate HIV cure-related research interventions. However, sex partners of cure-related trial participants might be at risk of acquiring HIV during ATIs. Addressing this risk is key to ensuring the continued success of trials involving ATIs and offer greater acceptability across multiple trials sites. In 2022, the Advancing Clinical Therapeutics Globally (ACTG) Network convened a Partner Protections Working Group (PPWG) to update the 2020 HIV transmission risk toolkit developed by Peluso and colleagues. In our review of the original toolkit, we identified new challenges and needs at the participant, partner and study levels, as well as new evidence on measures to address these needs and more advanced ethical thinking on partner protections in HIV cure-related trials with ATIs. Based on these findings, we developed an updated toolkit that will provide trial participants and their partners with better support to address new and unfamiliar situations and protect partners from undue harm. We present this toolkit, make it available as a resource for cure-related trials with ATIs and discuss possible future directions.